Inside the child sex trade - Journeyman Pictures ([United Kingdom] : Journeyman Pictures, 2004)
This video gauined rare access to Diana and Lina, two teenage prostitutes at a brothel in Batam. Focusing on the girls' plight and the mission to save them, they filmed every event leading to the girls' rescue. It's a confronting and harrowing expose of young children lured into a life of prostitution
Title from container
Keywords: Child prostitution; Prostitution; Sex crimes; Street children -- Crimes against